Development of palm oil based anti-corrosion material for underwater protection / Najmiddin Yaakob - Yaakob, Najmiddin (2007)
Corrosion problem has become a normal scenario faced by industrial chemical companies especially refineries. Petroleum refineries spend millions of Ringgits to protect the underground pipelines from being corroded. To cut down cost, a new formulation of anti-corrosion material has been developed where the main constituents were from crude palm oil (CPO). Naturally, CPO consists of 50% saturated fatty acids, 40%) mono-unsaturated and 9% polyunsaturated and approximately 1% of other components. The anti-corrosion formulation consists of CPO, epoxy and diethylenetriamine (DETA). Epoxy is produced by the reaction of bisphenol A with epichlorohydrin in an alkaline medium. DETA crosslinks the epoxy molecules and reacts with CPO to produce an imidazole derivative. A new anti-corrosion formula was developed from the synergist effect of combining DETA and CPO. Higher content in fatty acids causes more imidazole derivatives to be formed, which is the main factor in reducing corrosion rate. In order to increase the free fatty acid contents, the palm olein was blown with oxygen for few hours. The formulated anti-corrosion material was tested in various kinds of corrosive environment such as 1 M HC1 and sea water. For inhibitor, different concentrations at 2 g/L, 3 g/L and 4 g/L of inhibitor were analyzed in order to determine the inhibition efficiency. The temperatures for the corrosion environment were studied at 30°C, 50°C and 70°C. The inhibition efficiency was determined by using the Tafel analysis. A weight loss measurement was also conducted using mild steel coupons where the coupons were immersed in 1 M HC1 and seawater for 7 days. Results for the blown palm olein showed a significant increase in the free fatty acid contents from 34.19% to 50.71%). In 1 M HC1, the epoxy-blown olein sample showed a significant result as compared to that other inhibitors samples with an inhibition efficiency ranges from 89% to 94% In seawater, the inhibition efficiency ranges from 62% to 85% at 30°C, 50°C and 70°C. The optimum concentration for the epoxy-blown olein inhibitor sample was obtained at 3 g/L and 4 g/L.